MERIT SYSTEM: - Nurul Badria Ulfa; Denok Kurniasih (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2023)
The merit system is human resource management, which is used as a form of qualification by looking at workability to fill the position. This study looks at the effectiveness of implementing the open selection for JPT Pratama Aceh in 2022 in the new normal era and the factors influencing implementing the JPT Pratama selection. This study uses a qualitative descriptive approach with data collection techniques through the variable records of books, papers, journals, newspapers, and so on. The research analysis technique uses an interactive analysis model. The results of the study show that the implementation of open selection for JPT Pratama within the Government of Aceh in 2022 includes the announcement of open selection, participant registration, paper writing, LGD, psychometric tests, interview tests, and announcement of selection results. Then, three factors influence the effectiveness of implementing open selection for JPT Pratama in the Government of Aceh: accountability, infrastructure, technology and transparency.